A Jigsaw-Based Sensor Placement Algorithm for Wireless Sensor Networks. (5th November 2013) - Huang, Shih-Chang; Chang, Hong-Yi; Wu, Kun-Lin
Current deterministic sensor deploying methods always include the uncovered space greedily to reduce the number of deployed sensors. Because the sensing area of each sensor is circle-like, these greedily methods often divide the region of interest to multiple tiny and scattered regions. Therefore, many additional sensors are deployed to cover these scattered regions. This paper proposes a Jigsaw-based sensor placement (JSP) algorithm for deploying sensors deterministically. Sensors are placed at the periphery of the region of interest to prevent separating the region of interest to isolated regions. An enhanced mechanism is also proposed to improve the time complexity of the proposed method. The scenarios with and without obstacles are evaluated. The simulation results show that the proposed method can cover the whole region of interest with fewer deployed sensors. The effective coverage ratio of JSP method is less than 2. It is better than the maximum coverage method and the Delaunay triangulation method. The deploying sensors have more efficient coverage area, and the distribution of the incremental covered area is close to normal distribution.